2020
DOI: 10.1186/s12967-020-02610-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing cancer genetic somatic mutation test ordering by cancer physician

Abstract: Background Clinical whole exome sequencing was introduced in an Australian centre in 2017, as an alternative to Sanger sequencing. We aimed to identify predictors of cancer physicians’ somatic mutation test ordering behaviour. Methods A validated instrument assessed somatic mutation test ordering, genomic confidence, perceived utility of tumour molecular profiling, and percent of patients eligible for targeted therapy. A cash incentive was included… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…Lowest confidence was reported for tasks related directly to genetic testing and counselling, such as ordering tests and interpreting the results. These findings are congruent with similar surveys of GPs, oncologists (Demeshko et al, 2020) and obstetricians/gynaecologists (Nippert et al, 2011b). According to the COM-B model, failure to address the low confidence in genetic tasks would negatively affect successful uptake of providing genetic testing by clinicians.…”
Section: Discussionsupporting
confidence: 90%
“…Lowest confidence was reported for tasks related directly to genetic testing and counselling, such as ordering tests and interpreting the results. These findings are congruent with similar surveys of GPs, oncologists (Demeshko et al, 2020) and obstetricians/gynaecologists (Nippert et al, 2011b). According to the COM-B model, failure to address the low confidence in genetic tasks would negatively affect successful uptake of providing genetic testing by clinicians.…”
Section: Discussionsupporting
confidence: 90%
“…However, another possibility may be that healthcare personnel are uncomfortable dealing with genetic testing and the resulting findings. Numerous studies have shown that healthcare personnel, especially in the primary care setting, do not feel adequately equipped to order genetic tests or interpret, communicate, and follow up on such results ( Overby et al, 2014 ; George et al, 2015 ; Hamilton et al, 2017 ; Hann et al, 2017 ; Briggs et al, 2018 ; Hauser et al, 2018 ; Laforest et al, 2019 ; Menko et al, 2019 ; Demeshko et al, 2020 ). Reservations regarding insurance discrimination and the social impact the findings might have for the patient play a role as well, although we note that only one person in the results herein asked to have no mention of the finding in the medical record.…”
Section: Discussionmentioning
confidence: 99%
“…One qualitative study showed that healthcare providers believed experience working with genomics increased genomic confidence levels [ 38 ]. In Australia, a study showed that the frequency with which cancer physicians ordered genetic testing was associated with increased genomic confidence levels, however, it was unclear whether genomic confidence was a cause or effect of test ordering behaviour [ 26 ]. Similarly, a study in the United States reported genetic test ordering to be a key predictor of genomic confidence in family physicians [ 18 ].…”
Section: Discussionmentioning
confidence: 99%